(untitled) (Konferensiyalar | Conferences, 2024)
In the realm of language education, addressing the diverse needs of learners while fostering speaking proficiency presents a multifaceted challenge for teachers. This article explores the challenges faced by university teachers in balancing individual learners’ needs in speaking classes and underscores the importance of considering learner differences in promoting differentiated instruction.